Wnt1 inhibits vascular smooth muscle cell calcification by promoting ANKH expression - Chen, Beidong; Zhao, Yang; Han, Duanyang; Zhao, Ban; Mao, Yonghui; Cui, Zhong-Kai; Chu, Yun-Chin; Feng, Lu; Yin, Sen; Wang, Cun-Yu; Wang, Xian; Xu, Ming-Jiang; et al. (Journal of molecular and cellular cardiology, 2019)
Wnt signaling plays a critical role in vascular calcification (VC). Wnt factors induce different physiological and pathological effects on cardiovascular functions. Wnt1, a ligand of Wnt/β-catenin signaling, promotes pro-angiogenesis and reduces myocardial infarction. The role of Wnt1 on VC in chronic kidney disease (CKD) is not fully understood. We used human vascular smooth muscle cells (VSMCs) and a rat model of chronic renal failure (CRF), and observed a native protective mechanism by which VC is reduced via the activation of Wnt1 and its transcriptional target ANKH inorganic pyrophosphate transport regulator (ANKH) gene. ANKH is an essential calcification inhibitor that effluxes inorganic pyrophosphate (PPi) from VSMCs to play an inhibitory role in VC. Vascular ANKH and plasma PPi were significantly downregulated in the rat model of CRF. The knockdown or inhibition of ANKH reversed the effect of Wnt1 on VC in VSMCs. Clinical analysis revealed low plasma levels of Wnt1 and PPi were associated with CKD in patients. Applying a Wnt/β-catenin signaling agonist can alleviate the progression of VC. This work reveals the ANKH regulation of Wnt1 in VSMCs is essential for blocking VC. Our findings may contribute to the development of medications that target Wnt signaling and/or ANKH to inhibit VC. •Novel mechanism of Wnt1 protects against vascular calcification.•ANKH, a vascular calcification inhibitor, is a target gene of Wnt1/β-catenin signal.•Agonist of Wnt/β-catenin signal is a potential medicine for vascular calcification.